2011
DOI: 10.1126/science.1203161
|View full text |Cite
|
Sign up to set email alerts
|

Attention But Not Awareness Modulates the BOLD Signal in the Human V1 During Binocular Suppression

Abstract: Although recent psychophysical studies indicate that visual awareness and top-down attention are two distinct processes, it is not clear how they are neurally dissociated in the visual system. Using a two-by-two factorial functional magnetic resonance imaging design with binocular suppression, we found that the visibility or invisibility of a visual target led to only nonsignificant blood oxygenation level-dependent (BOLD) effects in the human primary visual cortex (V1). Directing attention toward and away fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
176
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(187 citation statements)
references
References 29 publications
9
176
1
1
Order By: Relevance
“…Another possible explanation that we cannot completely exclude here is that in some cases, fMRI mapping might not be sufficiently sensitive to detect weak visually induced activity in early visual areas. This is probably not the complete explanation, however, for several reasons: (i) We calculated the BOLD signal-to-noise ratio (SNR) in the areas of interest in all patients and found them to be within the range obtained in controls with AS; (ii) the variance explained of voxels corresponding to these visual field locations is within the range obtained in nonvisually responsive areas; and (iii) previous studies have shown that BOLD signal amplitude correlates well with visual stimulus perception (50,51), and in some cases even subthreshold stimuli elicit significant modulation in early visual areas (52). Do (Spared) Area V1 pRFs Change After the Lesions?…”
Section: Discussionmentioning
confidence: 91%
“…Another possible explanation that we cannot completely exclude here is that in some cases, fMRI mapping might not be sufficiently sensitive to detect weak visually induced activity in early visual areas. This is probably not the complete explanation, however, for several reasons: (i) We calculated the BOLD signal-to-noise ratio (SNR) in the areas of interest in all patients and found them to be within the range obtained in controls with AS; (ii) the variance explained of voxels corresponding to these visual field locations is within the range obtained in nonvisually responsive areas; and (iii) previous studies have shown that BOLD signal amplitude correlates well with visual stimulus perception (50,51), and in some cases even subthreshold stimuli elicit significant modulation in early visual areas (52). Do (Spared) Area V1 pRFs Change After the Lesions?…”
Section: Discussionmentioning
confidence: 91%
“…For instance, binocular rivalry studies have shown that attention affects the likelihood of observing suppression arising from competition (Ling & Blake, 2012) and that attention modulates rivalry-dependent responses in V1 (Watanabe, Cheng, Murayama, Ueno, Asamizuya, Tanaka, & Logothetis, 2011;Zhang, Jamison, Engel, He, & He, 2011). Some of these studies posit that attention is necessary for competition to occur (Zhang et al, 2011), while others posit that attention simply enhances suppression resulting from competition (Ling & Blake, 2012).…”
Section: Laterality and Attentionmentioning
confidence: 99%
“…More surprisingly, the study also reported that perceptual suppression left V1 responses altogether unaffected, which contradicts earlier findings (see review by Tong et al [59]). Watanabe et al [53] concluded that those earlier findings must have reflected an artefact caused by a reduction of attention concurrent with rivalry suppression, and that rivalry suppression, in itself, does not modulate V1 activity. What is unsatisfying about this conclusion, however, is that Watanabe et al failed to observe suppression-related modulation of V1 activity even in their condition requiring observers to attend to the grating's location, an instruction that exactly matches that of earlier studies that did find such modulation.…”
Section: Concern 2: Distinguishing Abolished Awareness From Inattentionmentioning
confidence: 99%
“…Using a design very similar to that of van Boxtel et al [23], Watanabe et al [53] also independently manipulated attention and stimulus awareness, now using fMRI to measure cortical activity in human V1. In this case, the design led to the conclusion that modulations of V1 activity that co-occur with absence of awareness are entirely due to inattention, not unawareness.…”
Section: Concern 2: Distinguishing Abolished Awareness From Inattentionmentioning
confidence: 99%